Dynamic energy balance of a building under the influence of changes in the thermal inertial properties of the building envelope and heating modes - Deshko, V.; Bilous, I.; Hetmanchuk, H.; Hurieiev М. (Energy and Automation, 2025)
Energy efficiency in buildings is one of the key areas for reducing energy consumption and greenhouse gas emissions. Optimisation of heat flows and heating modes contributes to increasing the energy efficiency of buildings and reducing heating costs. The purpose of the study is to conduct a parametric analysis of the components of the building heat balance and heat flows in rooms with different thermal properties. The research methods include the use of DesignBuilder software, which is based on the EnergyPlus platform. On the basis of this software, a non-stationary multi-zone energy model of a multi-storey building was created, which is used to determine the components of the energy balance of a representative room at different parameters of structural elements and operating modes of the heating system. The results of the study showed that the energy consumption of north-facing buildings for heating purposes is on average 34.8% to 38.3% higher than that of south-facing buildings, depending on the wall thickness. The use of intermittent heating modes can reduce heat consumption by up to 19.9%, depending on the thickness and type of building. It was also found that insulation of external walls and replacement of windows with energy-efficient ones have a much greater potential for reducing energy consumption than changing the mass of internal walls. One of the south-facing models with a constant heating mode in January showed a 39.2% reduction in heating costs compared to a similar model without insulation. The additional introduction of intermittent heating modes can reduce energy consumption by up to 22.3% for south-facing rooms and up to 21.4% for north-facing rooms. The obtained results can be used to develop recommendations for optimal regulation of heating modes for premises with different characteristics of external and internal walls, which will contribute to the energy efficiency of buildings. Key words: EnergyPlus, dynamic modelling, heat losses, solar heat gain, climate data, energy efficiency